The readiness to adopt green intelligent and sustainable manufacturing for agriculture in industry 4.0 - Hammad, Muhammad Yahya; Muhammad Ashraf, Fauzi; Puteri Fadzline, Muhamad Tamyez; Ahmad Nazif, Noor Kamar; Syed Radzi, Rahamaddulla (American Institute of Mathematical Sciences, 2025)
The desire to balance environmental sustainability and food security is causing a significant upheaval in the agricultural sector. This study investigated how prepared stakeholders are to embrace agriculture in Industry 4.0, which integrates green, intelligent, and sustainable technologies like blockchain, IoT, and AI. Although these advances promise increased resilience and efficiency, they present significant obstacles to implementation, such as inadequate infrastructure, socioeconomic inequality, and a lack of technology awareness. This study highlights these technologies' theoretical and managerial implications and finds critical gaps using bibliometric and thematic analysis. To overcome adoption obstacles, it emphasizes the significance of inclusive policies, strategic alliances, and capacity-building programs. The study concludes that these impediments must be addressed to secure food systems for future generations and align agriculture with global sustainability goals. Longitudinal studies, stakeholder-centric methodologies, and investigating emergent technology synergies are among the suggestions for future research.